Theoretical Basis For Ensuring Economic Security And Competitiveness of The Region in Foreign Trade Activities - Olga Makarova1; Yulia Makarova1; Svetlana Gladkova2; Yulia Dubolazova1 (Communications of International Proceedings, 2020)
The article discusses competitiveness at the present stage. The analysis made it possible to systematize the views of individual domestic and foreign authors on the disclosure of the concept of competitiveness, methods of its assessment. The authors formulated a definition of the competitiveness of enterprises, taking into account the level of offenses in foreign economic activity and highlighted other approaches to the definition of the concept of competitiveness: legal, mathematical, socio-psychological, organizational and managerial, economic and financial. The article considers factors and conditions influencing competitiveness, including the region, through indices of comparative advantages. The Bell Balassa Index, Lafey Index, PCA Index, WEF Competitiveness Index were considered. Global Overview, "Growth Index. Factors that represent potential threats to Russia's foreign economic security include health and primary education, labor market efficiency, technological readiness, business and macroeconomic environment. Disclosing ensuring the competitiveness of enterprises taking into account countering violations in foreign trade activities, the classification of violations in foreign trade activities was clarified.
Keywords: Competitiveness; Economic Security; Foreign Trade; Threats; Risks